The rationale for developing a programme of services by and for Indigenous men in a First Nations community. (June 2019) - George, Julie; Morton Ninomiya, Melody; Graham, Kathryn; Bernards, Sharon; Wells, Samantha
While mental well-being is recognized as a significant public health priority in numerous Indigenous communities, little work has focused on the mental health needs of Indigenous men. In this article, we describe results from the mixed-methods research used to inform the development of mental wellness programming for boys and men. Quantitative and qualitative data from two studies conducted in Kettle & Stony Point First Nation, an Indigenous community in southern Ontario, Canada, were used to (a) understand factors that contributed to issues of mental health, substance use and violence for men, (b) understand men's experiences accessing and seeking supports and services, and (c) identify ways to address mental health, substance use and violence among boys and men in the community. We show how results from two studies ignited a group of men to develop a culturally strong and strengths-based programme of services as well as a wellness strategy for boys and men in the community.